Analytical determination of the frequency of short circuits of the arc at surfacing in gas dioxide with welding pool mechanical oscillations - V. A. Lebedev; S. V. Novikov; S. A. Loy (Журнал інженерних наук)
A hypothesis has been put forward that it is possible to reduce the degree of splashing when surfacing into carbon dioxide due to the setting of the frequency characteristics of the oscillation of the weld pool. Equations are presented that are the result of theoretical research, on the basis of which an expression for the short-circuits frequency of the inter-arc gap in the process of surfacing by on a direct current is determined. On the basis of brief literature analysis of the works past years old its is showed that the frequency imposed on the welding pool has to detected by crystallization frequency near the crystallization front melt which is detected by a surfacing velocity and crystallization characteristics of weld pool metal. Due to the fact that for present day the strict theory of crystallization in the conditions outer oscillations haven't created, the dependencies for an amplitude-frequency characteristic’s determining which were got by different researchers have been presented. The example of calculation of an arc burning time and time of short circuit in period of surfacing process have been presented. On the basis of that, frequency of short circuits has been determined.